Political Education Ahead of the 2024 Regional Election at SMAS Budi Satrya Medan - Silalahi, Marly Meani; Pinem, Windawati; Sembiring, Gadis Prasiska (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
This research aims to provide political education to students at SMAS Budi Satrya ahead of the 2024 Regional Elections. The problem in this study is that the political participation of novice voters in elections and regional elections is still low. This is due to the limited knowledge they have about elections/regional elections. Therefore, political education is needed for novice voters to increase their political participation. This political education is expected to increase the political awareness of students to participate in the Regional Election process. Data collection techniques are carried out by interviews and observations. Data validation is carried out by data triangulation. The results of this study show that political education has an impact on the knowledge and interest of students of SMAS Budi Satrya Pilkada.